2016
DOI: 10.1103/physreva.94.062116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bath temperature on the decoherence of quantum dissipative systems

Abstract: We report an anomalous decoherence phenomenon of a quantum dissipative system in the framework of a stochastic decoupling scheme along with a hierarchical equations-of-motion formalism without the usual Born-Markov or weak coupling approximations. It is found that the decoherence of a two-qubit spin-boson model can be reduced by increasing the bath temperature in strongcoupling regimes. For the weak-coupling situation, we find that the bath temperature may enhance the decoherence. This result is contrary to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 49 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…Thus, the HEOM can be viewed as an exactly numerical treatment of the quantum dissipative dynamics. In recent years, the HEOM approach has been successfully used to study the anomalous decoherence phenomenon in a nonlinear spin-boson model [51], the quantum Zeno and anti-Zeno phenomena in a noisy environment [52], as well as the influence of counter-rotating-wave terms on the measure of non-Markovianity [53].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the HEOM can be viewed as an exactly numerical treatment of the quantum dissipative dynamics. In recent years, the HEOM approach has been successfully used to study the anomalous decoherence phenomenon in a nonlinear spin-boson model [51], the quantum Zeno and anti-Zeno phenomena in a noisy environment [52], as well as the influence of counter-rotating-wave terms on the measure of non-Markovianity [53].…”
Section: Introductionmentioning
confidence: 99%
“…One commonly believed concept is that the bath temperature can speed up the destruction of quantum coherence. However, some studies have shown that the bath temperature is able to reduce the decoherence in some quantum dissipative systems [26,27]. This result is contrary to the common recognition that a higher bath temperature always induces a more severe decoherence and suggests that the bath temperature plays a very intricate role in quantum dissipative systems.…”
Section: Introductionmentioning
confidence: 80%
“…17 reduces to the hierarchical equations in Ref. [27]. This approximation is reliable when the bath temperature is not very low.…”
Section: Appendix: Methodologymentioning
confidence: 92%
See 1 more Smart Citation
“…with χ stands for the coupling strength between the quantum subsystem and the bath, parameter ω c is the cutoff frequency. In this case, the bath correlation function ξ(t) is given by [40,[63][64][65]…”
Section: A Self-adjoint Coupling Casementioning
confidence: 99%